A study of role of non-operative management in blunt abdominal trauma with solid organ injury - Bansod, Atish N.; Umalkar, Rohan; Shyamkuwar, Ambrish T.; Singade, Amar; Tayade, Priyanka; Awachar, Neha (International Surgery Journal, 2018)
Background: The present study of role of non-operative management in blunt abdominal trauma with solid organ injury was done to assess the feasibility and safety of non-operative management in hemodynamically stable patients and identify the causes, predictive factors to delineate the rate of non-operative management failure. Methods: A longitudinal observational study was carried out from September 2013 to November 2015. All cases of blunt trauma abdomen with ultrasonological e/o solid organ injury and were hemodynamically stable were included in study. Results: Total 138 cases presented with a history of blunt trauma abdomen of which 56 cases had ultrasonological evidence of solid organ injury. 8 cases were excluded as 6 of these were hemodynamically unstable at presentation while 1 had bowel perforation and another had severe head injury all requiring operative management. Maximum cases were of age group 21-30 years (41.66%) and 31-40 years (31.25%). 42 (87.5%) cases were male and 6 (12.5%) cases of 48 were females. 28 (66.67%) cases presented as Road Traffic Accident. 28 (66.67%) cases had abdominal pain as the commonest symptom while tenderness in 38 (79.17%) cases and tachycardia in 30 (75%) cases was the predominant sign. Most injuries were seen in spleen 23 (47.92%) cases f/b Liver with 14 (29.12%). Conservative management was successful in 40 (83.33%) cases and failed in 8 (16.67%) cases. Mortality of the study was 1 (2.08%) case. Conclusions: Non-operative strategy is a successful approach in patients who are hemodynamically stable and authors strongly recommend it.